A comprehensive breath test that confirms recent use of inhaled cannabis within the impairment window - Michael W. DeGregorio (Nature Portfolio, 2021)
Abstract Legalization of cannabis for medicinal and/or recreational use is expanding globally. Although cannabis is being regulated country by country, an accurate recent use test with indisputable results correlated with impairment has yet to be discovered. In the present study, a new approach for determining recent cannabis use within the impairment window after smoking was developed by studying 74 subjects with a mean age of 25 years and average use history of 9 years. Horizontal gaze nystagmus was evaluated along with subject self-assessments of impairment, and blood and breath samples were collected before and after smoking cannabis. Breath and blood pharmacokinetic parameters and cannabinoid profiles determined recent use within the impairment window. No subjects were positive for recent use pre-smoking, although all subjects had detectable cannabinoids in breath samples. We describe an inhaled cannabis recent use test that correlates with impairment and helps protect against wrongful prosecution and workplace discrimination.